2021
DOI: 10.1002/mp.15069
|View full text |Cite|
|
Sign up to set email alerts
|

Report of AAPM Task Group 219 on independent calculation‐based dose/MU verification for IMRT

Abstract: Independent verification of the dose per monitor unit (MU) to deliver the prescribed dose to a patient has been a mainstay of radiation oncology quality assurance (QA). We discuss the role of secondary dose/MU calculation programs as part of a comprehensive QA program. This report provides guidelines on calculationbased dose/MU verification for intensity modulated radiation therapy (IMRT) or volumetric modulated arc therapy (VMAT) provided by various modalities. We provide a review of various algorithms for "i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
87
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(101 citation statements)
references
References 109 publications
(317 reference statements)
0
87
0
3
Order By: Relevance
“…Development of dose calculation algorithms over the years made IDC the only possibility to perform QA in the patient geometry. Nowadays, it seems that the radiation therapy community in general (including both conventional and LIBT), is moving back to the roots of PSQA using IDC, rather than experimental PSQA [40]. In the framework of the Imaging and Radiation Oncology Core (IROC) [41], it was demonstrated that IDC was 12 times more sensitive at detecting treatment failures for IMRT than experimental PSQA.…”
Section: Discussionmentioning
confidence: 99%
“…Development of dose calculation algorithms over the years made IDC the only possibility to perform QA in the patient geometry. Nowadays, it seems that the radiation therapy community in general (including both conventional and LIBT), is moving back to the roots of PSQA using IDC, rather than experimental PSQA [40]. In the framework of the Imaging and Radiation Oncology Core (IROC) [41], it was demonstrated that IDC was 12 times more sensitive at detecting treatment failures for IMRT than experimental PSQA.…”
Section: Discussionmentioning
confidence: 99%
“…For heterogeneous geometries, we will need to develop additional tools to deal with the situation where lung tumors are surrounded by large air cavities and the planar dose distributions may be significantly affected by the electron return effect. A recent study has looked at replacing two-dimensional gamma analysis with threedimensional-based analysis, such as three-dimensional gamma and dose-volume histogram (DVH) comparisons (21) to provide a more realistic comparison with the planning criteria as also recommended by recently published TG219 (9). We used planar dose for gamma analysis, which can be more sensitive to the magnetic field effect and the dose gradient in the plane normal direction.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate quality assurance (QA) criteria, such as gamma pass rate, have not yet been established for MR-guided radiotherapy. To ensure the safety of the delivery (9), several in-house solutions were developed by different institutions to perform an independent monitor unit (IMU) QA (4,8,(10)(11)(12)(13). Most of them perform the IMU check by using dose engines from clinical TPSs or commercial QA software, such as Raystation Collapsed Cone (11), Oncentra Collapsed Cone (12), Mobius 3D (13), and RadCalc (8).…”
Section: Introductionmentioning
confidence: 99%
“…Quality assurance (QA) programs are designed to improve the quality and the safety of radiation treatments, including machine- and patient-specific QA [1] , [2] . The latter can be performed prior to treatment (pre-treatment verification) or during beam delivery (in-vivo dosimetry, IVD) [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%